1999
DOI: 10.17221/9706-pps
|View full text |Cite
|
Sign up to set email alerts
|

The fusarloses of barley with emphasis on the content of trichothecene

Abstract: The infestation of barley grains by fungi of the genus Fusarium was studied on malting barley from Kromei'iz (360 samples) and one sample from Kojet!n in Czech Republic. Most frequent species in the season 1997-1998 were: F. culmorum (over 70% of the isolates), F. poae (over 20% of the isolates), F. avenaceum  (over 2%). Much less frequent were: F. stilboides  v. stilboides, F. aqaeductum v. aqaeductum, F. merismoides v. merismoides and F. gigas. The isolates of F. culmorum were highly pathogenic when barley w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 5 publications
0
6
0
4
Order By: Relevance
“…Fusariózy klasů byly zaznamenány ve všech oblastech pěstování obilnin, např. v Rusku [15], Indii [16], Mexiku [17], Polsku [18], České republice [10].…”
Section:  3 Results and Discussionunclassified
See 3 more Smart Citations
“…Fusariózy klasů byly zaznamenány ve všech oblastech pěstování obilnin, např. v Rusku [15], Indii [16], Mexiku [17], Polsku [18], České republice [10].…”
Section:  3 Results and Discussionunclassified
“…The species most often isolated in our experiments was F. culmorum (46 % and 30 %). Hýsek et al [10] reported on F. culmorum (70 %) and F. poae (20 %) as the Fusarium species most often isolated in the Czech Republic and Richardson [12] also recorded F. culmorum as the most frequent contaminant of barley seeds, and named F. graminearum, F. moniliforme, M. nivale and F. poae as other species. In our study, only 7 % of undisinfected seeds and 2 % of surface disinfected ones out of the total number of fusaria were infected by F. poae whereas F. graminearum and F. avenaceum were present in higher proportions.…”
Section:  3 Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Složení druhové spektra se může lišit v rámci roku a lokality. Hýsek [18] uvádí na ječmeni v České republice jako nejčastěji izolované druhy F. culmorum a F. poae. Schilling [19] uvádí jako nejčastější druh v Německu F. graminearum a v Holandsku F. avenaceum.…”
Section:  3 Výsledky a Diskuseunclassified